The Role of Self-esteem and Fear of Negative Evaluation in Compulsive Buying - Biolcati, Roberta (Frontiers in Psychiatry, 2017)
Compulsive buying is a relatively new addictive disorder that interferes with everyday functioning and may result in serious psychological and financial problems (McElroy et al., 1994). A very few data are currently available regarding this behavioral addiction. This study investigated gender differences in the relationships between contingent self-esteem (CSE), fear of negative evaluation (FNE) and compulsive buying (CB). Participants included 240 Italian adults (170 female, M age = 33.80) who responded to self-report questionnaires. The results showed that women scored higher on CSE and FNE scales than men. No gender differences were found in compulsive buying tendencies. CSE and FNE were positively related to CB. Furthermore, structural equation modelling confirmed the evidence on CSE as a strong predictor of CB for both genders. Interestingly, FNE seems to play a mediating role between CSE and compulsive buying behaviors only for women. These findings highlight the importance of studying self-esteem in compulsive buying tendencies to inquire more deeply into the underlying mechanisms of some compulsive behaviors.